Evaluation of the Content and Accessibility of Web Sites for Accredited Orthopaedic Trauma Surgery Fellowships. (2nd May 2018) - Shaath, M. Kareem; Yeranosian, Michael G.; Ippolito, Joseph A.; Adams, Mark R.; Sirkin, Michael S.; Reilly, Mark C.
Abstract : Background: Orthopaedic trauma fellowship applicants use online-based resources when researching information on potential U.S. fellowship programs. The 2 primary sources for identifying programs are the Orthopaedic Trauma Association (OTA) database and the San Francisco Match (SF Match) database. Previous studies in other orthopaedic subspecialty areas have demonstrated considerable discrepancies among fellowship programs. The purpose of this study was to analyze content and availability of information on orthopaedic trauma surgery fellowship web sites. Methods: The online databases of the OTA and SF Match were reviewed to determine the availability of embedded program links or external links for the included programs. Thereafter, a Google search was performed for each program individually by typing the program's name, followed by the term "orthopaedic trauma fellowship." All identified fellowship web sites were analyzed for accessibility and content. Web sites were evaluated for comprehensiveness in mentioning key components of the orthopaedic trauma surgery curriculum. By consensus, we refined the final list of variables utilizing the methodology of previous studies on the topic. Results: We identified 54 OTA-accredited fellowship programs, offering 87 positions. The majority (94%) of programs had web sites accessible through a Google search. Of the 51 web sites found, all (100%) described their program. Most commonly, hospital affiliation (88%), operative experiences (76%), and rotation overview (65%) were listed, and, least commonly, interview dates (6%), selection criteria (16%), on-call requirements (20%), and fellow evaluation criteria (20%) were listed. Programs with ≥2 fellows provided more information with regard to education content (p = 0.0001) and recruitment content (p = 0.013). Programs with Accreditation Council for Graduate Medical Education (ACGME) accreditation status also provided greater information with regard to education content (odds ratio, 4.0; p = 0.0001). Otherwise, no differences were seen by region, residency affiliation, medical school affiliation, or hospital affiliation. Conclusions: The SF Match and OTA databases provide few direct links to fellowship web sites. Individual program web sites do not effectively and completely convey information about the programs. The Internet is an underused resource for fellow recruitment. The lack of information on these sites allows for future opportunity to optimize this resource.